Perancangan Desain Kemasan Produk Hand Cream (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2025)
Successful packaging design is not only a determinant of a product's success in the market, especially in the beauty industry such as hand cream. The role of aesthetically pleasing and functional packaging design is crucial in influencing consumer purchasing decisions. Therefore, a marketing strategy focused on packaging design becomes key to enhancing product appeal and sales. The strategic use of mockups in the design phase allows designers to test and evaluate concepts digitally without the need for physical prototypes. The advantage of mockups lies in their ability to provide a realistic preview, expediting the design and development process. The aspects of packaging design are critical in creating a visually compelling and convincing experience for consumers. This research, employing a descriptive approach and qualitative methods, aims to explore the appropriate approach in designing hand cream packaging. The hope is that this research serves as a significant initial step in the development of hand cream packaging design, ensuring the product not only meets aesthetic standards but also competes effectively in a competitive market.